2016
DOI: 10.3390/ma9110878
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing a Test Method to Evaluate Resistance of Pervious Concrete to Cycles of Freezing and Thawing in the Presence of Different Deicing Salts

Abstract: The lack of a standard test method for evaluating the resistance of pervious concrete to cycles of freezing and thawing in the presence of deicing salts is the motive behind this study. Different sample size and geometry, cycle duration, and level of submersion in brine solutions were investigated to achieve an optimized test method. The optimized test method was able to produce different levels of damage when different types of deicing salts were used. The optimized duration of one cycle was found to be 24 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Erhan Guneyisi [7] reported that adding recycled aggregate to pervious concrete can improve its permeability. Pervious concrete is widely used in pavement engineering, and it has the advantages of reducing noise, reducing water accumulation, improving the environment, and supplementing groundwater sources [8,9]. It has strong gas permeability, the porosity is usually sizes less than 5 mm were screened.…”
Section: Introductionmentioning
confidence: 99%
“…Erhan Guneyisi [7] reported that adding recycled aggregate to pervious concrete can improve its permeability. Pervious concrete is widely used in pavement engineering, and it has the advantages of reducing noise, reducing water accumulation, improving the environment, and supplementing groundwater sources [8,9]. It has strong gas permeability, the porosity is usually sizes less than 5 mm were screened.…”
Section: Introductionmentioning
confidence: 99%
“…The use of natural aggregates is currently widespread in the manufacture of PC [6], but few studies have used RA [7]. As important quantities of construction and demolition waste are contaminating many ecosystems worldwide, it is imperative to recycle them and produce new building materials, recycled concrete [8].…”
Section: Introductionmentioning
confidence: 99%
“…The destruction of C2 and C3 was in the form of a spatter on the concrete's surface and, according to the literature [1,6,[8][9][10], covered only the surface layer of the hardened cement paste, which has a thickness of several millimeters. However, in C4, scaling of the top layer's surface took place until the 49th cycle and was followed by volumetric destruction.…”
Section: The Effect Of the Sp On The Scaling Resistancementioning
confidence: 99%
“…This destruction is most often manifested by chipping on the concrete's surface. Even when the structure is destroyed due to the very strong effects of a freeze-thaw cycle when thawing agents are used, such destruction only covers the hardened cement paste's surface layer, which has a thickness of several millimeters [1,6,[8][9][10]. The mechanism that underlies the destruction of concrete as a result of peeling is different from the volumetric effect of a freeze-thaw cycle, which occurs as a result of internal crystallization and causes a decrease in strength [4,11].…”
Section: Introductionmentioning
confidence: 99%